Development of a prototype for web-based design flood estimation expert system / Hasniza Ismail - Ismail, Hasniza (2003)
Reliable estimate of the magnitude and freqiiency of floods, commonly called 'Design Flood Estimation' is important for planning and design of hydraulic structures. Under-designed structure may results in disaster, whilst over-designed could be too costly. One of the locally developed applications on Design Flood Estimation is the DeFlood ver. 1.0. The application adopts the techniques employed by the Malaysian Drainage and Irrigation Department and provides an easy and fast approach to analyze and compute results for Design Flood Estimation. Techniques implemented are Regional Flood Frequency Analysis Method, Rational Method, Triangular Hydrograph Method and Revised Regional Flood Frequency Analysis Method. However, it inherited several limitations such as not user-friendly, stand-alone system and difficult to access. Based on the limitations, Design Flood Estimation Expert System on the web is develop so that the application could be more user-friendly and easy to access. DFEES idivided into expert and beginner level. Expert module is simpler compared to beginner module. Beginner module is provided with step-by-step operation as well as providing short tutorial.